Prediction of Vegetable Supply in Henan Province Based on PSO-GM (1, N) Model. (25th August 2021) - Guo, Xueqiang; Li, Bingjun
Abstract : GM (1, N ) model is one of the grey prediction models considering the influence of many factors. This paper improves GM (1, N ) model and constructs PSO-GM (1, N ) model. Firstly, Lasso method is used to select the influencing factors, then the priority of influencing factors and the value of parameter N in GM (1, N ) model are determined, and finally PSO method is used to optimize GM (1, N ) model. Taking the vegetable supply in Henan Province as the research object, this paper makes an empirical test by using PSO-GM (1, N ) model. The results show that the key factors affecting the vegetable supply in Henan Province are the number of rural employees, highway mileage, and application of pesticide. The vegetable supply in Henan Province will continue to show a steady growth trend in the next three years.